IMPACT OF PREJUDICE ON SOCIAL BEHAVIOR - Jain, Paras; Billaiya, Roshni; Jain, Shivangi (International Journal of Research -GRANTHAALAYAH, 2018)
Everyone whether it is human or animal influence by prejudice nature and behave socially according to prejudiced thinking. It influences negatively preventing to handle situations, persons with new perspective. It acts as barrier for nurturing new ideas and thinking development. It affects decision making power of a person. Present study is targeted to measure prejudice nature and finding its impact on social behavior.